The Challenges of Decentralization Fiscal Regulations: Experience from the Philippines - Elvira, Elvira; Susanto, Susanto; Soriano, Elmer Micu (BESTUUR, 2023)
This research aims to understand, analyze, and detail the experience of fiscal decentralization in Indonesia and the Philippines. It explores the main challenges faced in implementing fiscal decentralization policies and valuable lessons that can guide other third countries planning to expand their local entities' fiscal authority. By comparing the experiences of the two, we can explore the similarities and differences in approaches and analyze their impact on economic development and local empowerment. The results show that decentralization in the Philippines is comprehensive and has one of Southeast Asia's most substantial legal bases. Moreover, each tier or each type of local government has a rather direct relation to the central government, especially in fiscal relationships, and is relatively independent compared to other countries in the region.